2012
DOI: 10.24200/jams.vol17iss0pp33-43
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Rearing of Spiny Lobster, Panulirus homarus (Palinuridae) in Land-Based Tanks at Mirbat Station (Sultanate of Oman) in 2009-2010

Abstract: Two experiments on the rearing of the spiny lobster Panulirus homarus were conducted in land-based tanks at Mirbat Aquaculture Unit from June to December 2009 and January-December 2010. In the first experiment 14 lobsters with an average size of 64.9±7.4 mm CL and weight of 297.8±98.0 g were reared to an average of 71.7±7.2 mm CL and weight of 384.0±114.8 g over 187 days. In the second experiment 45 lobsters were reared from an initial length of 45.4±4.6 mm CL and weight of 118.9 g to a length 66.0±7.1 mm CL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The products obtained through the production pattern will produce continuous and sustainable lobster production. Moreover, water quality management by maintaining the temperature, pH, salinity, alkalinity, and optimal dissolved oxygen in the culture period can maximize lobster growth (Balkhair et al, 2012;Aji et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The products obtained through the production pattern will produce continuous and sustainable lobster production. Moreover, water quality management by maintaining the temperature, pH, salinity, alkalinity, and optimal dissolved oxygen in the culture period can maximize lobster growth (Balkhair et al, 2012;Aji et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design was complete randomized design with three treatments and two replications. The treatment was treatment modification according to Balkhair et al (2012), Sakthivel et al (2014), and Lee et al (2015) with stocking density showed in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…The adaptation period was performed for 14 days until the spiny lobster became active and had a good appetite. The feed which given to the spiny lobster was as many of 3% of total weight and the feeding frequency was once at 5 p.m. (Balkhair et al, 2012). The tanks used in this study was six tanks of fiber tanks size in 1.2×0.95×1 m 3 filled with 800 L of seawater.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…The descriptions of growth of P. homarus using a tagging method [20] or grow-out data [21][22][23][24][25][26][27][28] are rare and assessed growth only during a short period of the lobster life. The growth parameters especially the in VBGF estimated in the present study (Table 3) especially the asymptotic lengths (L inf ) for Al-Wusta and Al-Sharqiyah concur with majority of authors.…”
Section: Discussionmentioning
confidence: 99%